Case Report: Testicular teratoma with malignant transformation to melanoma and concurrent metastatic carcinoma of undetermined primary origin in a red deer (Cervus elaphus) - Criado, Miguel; Prieto, Paloma; Palomares, Juan José; Lopezosa, Desiderio; Zapico, David; Mendívil, Pedro; Benavides, Julio; Ferreras, M. Carmen; Espinosa, José (Frontiers in Veterinary Science, 2025)
Testicular teratomas are rare germ cell neoplasms composed of two or more embryonic germ layers—ectoderm, mesoderm, and endoderm. They are uncommon in domestic species, with only a few cases reported in wild mammals, and malignant transformation is rare. We report the case of a European red deer (Cervus elaphus), approximately 4 years of age, that presented with marked scrotal enlargement. Necropsy revealed an enlarged left testis weighing 3.29 kg. On sectioning, it showed complete loss of its normal architecture, with multiple multinodular solid areas and cystic regions containing dark fluid. An inguinal lymph node was diffusely darkly pigmented, while an iliac lymph node was enlarged and showed complete architectural effacement. Histopathological examination confirmed the presence of a teratoma with differentiation into tissues derived from all three germ layers. Additionally, two distinct cell populations with clear malignant features were identified in the testis and the iliac lymph node. Immunohistochemical and immunofluorescence studies were performed for their characterization. Antibodies used included pancytokeratin (PCK), Melan-A, vimentin (Vim), c-KIT receptor tyrosine kinase (CD117), S100 protein, and ionized calcium-binding adaptor molecule 1 (IBA1), some of which had not previously been used in this species. The results revealed a malignant transformation of the teratoma, with the presence of a poorly differentiated, invasive melanoma (Vim+, Melan-A+, S100−, and CD117−), accompanied by numerous melanophages (IBA1+) in the surrounding tissue and inguinal lymph nodes, and a concomitant metastatic carcinoma (PCK+), which was identified in the iliac lymph node of undetermined origin. To the best of our knowledge, there are no documented cases of testicular teratomas with these characteristics in wild species of the Cervidae family or in other animal species.